Nonlinear Distortions in Electroacoustic Devices - DOBRUCKI, Andrzej (Archives of Acoustics, 2011)
The task of electroacoustic devices is a transmission of audio signals. The transmitted signal should be distorted as little as possible. Nonlinear distortions are the distortions depending on signal level. The types of nonlinear distortions as well as their measures are presented in the paper. The weakest device in an electroacoustic chain is a loudspeaker. It causes the greatest degradation of the signal. It is usually the most nonlinear part of the electroacoustic system. The nonlinearities in loudspeakers are described in details. Other types of nonlinear distortions as transient intermodulation in power amplifiers and distortions caused by the A/C sampling are also presented.